Law and religion - Sandberg, Russell (Cambridge University Press, 2011)
"The worlds of law and religion increasingly collide in Parliament and the courtroom. Religious courts, the wearing of religious symbols and faith schools have given rise to increased legislation and litigation. This is the first student textbook to set out the fundamental principles and issues of law and religion in England and Wales. Offering a succinct exposition and critical analysis of the field, it explores how English law regulates the practice of religion. The textbook surveys law and religion from various perspectives, such as human rights and discrimination law, as well as considering the legal status of both religion and religious groups. Controversial and provocative questions are explored, promoting full engagement with the key debates. The book's explanatory approach and detailed references ensure understanding and encourage independent study. Students can track key developments on the book's updating website. This innovative text is essential reading for all students in the field"--Provided by publisher.